Principles of significant critical learning on continued teachers’ formation - Rocha, Marcelo Augusto; Salvi, Rosana Figueiredo (Geosaberes; Vol 9 No 17 (2018): Jan - AprDO - 10.26895/geosaberes.v9i17.627, 2017)
This article seeks to think about results of a teaching and learning approach applied at the continued formation of Geography teachers in Digital Information and Communication Technologies (DICT) in the context of Critical Significant Learning principles proposed by Moreira (2005). The course was structured to support the Technological and Pedagogical Knowledge of the TPACK (Technological Pedagogical Content Knowledge) Content as a result of an integrated knowledge vision articulated by Mishra & Koehler (2006). Based on a pedagogical context which seems to match the using of digital technologies with Valente's Learning Spiral (2005), with the contributions of Didactics of the Sciences, proposed by Zabala (1998) and with the Critical Significant Learning of Moreira (2005).
Keywords: Conhecimento Tecnológico e Pedagógico do Conteúdo, Aprendizagem Significativa Critica, Formação docente.